Developing glazes - Daly, Greg.; American Ceramic Society (London : Bloomsbury, 2013)
Chapter 1 - The journey begins Chapter 2 - Getting started Chapter 3 - Systems for testing Chapter 4 - Fluxes and colour Chapter 5 - Developing colour Chapter 6 - Oxide response in glazes Chapter 7 - Recipes
boek
Keywords: Glazes